Leaves of grass = 풀잎 - Lee, Hyo-seok (바이링궐 에디션 한국 대표 소설, 2015)
Leaves of Grass has long been considered a simple love story or else an escapist work of aestheticism. However, if we consider its emphasis on autonomy in the love between Chun-bo and Okshil in the context of the social and political situation in 1942, it can be interpreted as having political implications as well. ... Although Chun-bo and Ok-shil do not actively resist this system, they passively resist it by protecting their autonomous realm of love from the comprehensive network of the existing system